In-group evaluation and self-esteem of fraternity members in the University of the Philippines in the Visayas in Iloilo. - Doronila, Marie Pearl Marjorie L.; Sentina, Deceryl M. (2003.)
This study sought to find out the relationship between in-group evaluation and self-esteem of students in UPV Iloilo. The study was conducted in both Iloilo and Miag-ao campuses. The subjects were taken from members of fraternities in the university. The fraternities used in the study were UP Beta Sigma, UP Vanguard Fraternity, UP Hamili Brotherhood, UP Silak Brotherhood, UP Validus Amicitia, and UP Scintilla Juris Fraternity. There were 44 subjects in this study. 50% from the total number of members in each fraternity were taken. The subjects were chosen using simple random sampling (fishbowl method). Questionnaires consisting of three scales were administered to the subjects. The questionnaires were made up of the25-item Barkshade Self-esteem Evaluation Scale to measure personal self-esteem, the Collective Self-esteem Scale to measure collective self-esteem, and the Semantic Differential Scale to measure in-group evaluation. The findings of the study show that there is a high positive correlation between personal self-esteem and group goals, a negative correlation between personal self-esteem and leadership style, a negative correlation between personal self-esteem and group syntality, and a low degree of positive correlation between personal self-esteem and group cohesiveness. All in all, there is a low degree of positive correlation between in-group evaluation and personal self-esteem. Results also show that there is a negative correlation between personal self-esteem and collective self-esteem.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP in the Visayas, Miagao, Iloilo
Keywords: Fraternities -- UPV, Miag-ao, Iloilo